2019
DOI: 10.1103/physrevmaterials.3.090302
|View full text |Cite
|
Sign up to set email alerts
|

Electronic defects in Cu(In,Ga)Se2 : Towards a comprehensive model

Abstract: The electronic defects in any semiconductor play a decisive role for the usability of this material in an optoelectronic device. Electronic defects determine the doping level as well as the recombination centers of a solar cell absorber. Cu(In, Ga)Se 2 is used in thin-film solar cells with high and stable efficiencies. The electronic defects in this class of materials have been studied experimentally by photoluminescence, admittance, and photocurrent spectroscopies for many decades now. The literature results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(69 citation statements)
references
References 156 publications
(264 reference statements)
5
62
1
1
Order By: Relevance
“…Besides, the Cu In and Cu i have clear PL signatures (cf. Spindler et al 4 ) and do not correlate with the 200 ± 20 meV defect.…”
Section: Optoelectronics Of Cis Metastability Induced By Cyanidementioning
confidence: 92%
“…Besides, the Cu In and Cu i have clear PL signatures (cf. Spindler et al 4 ) and do not correlate with the 200 ± 20 meV defect.…”
Section: Optoelectronics Of Cis Metastability Induced By Cyanidementioning
confidence: 92%
“…Pohl et al calculated that In Cu in CuGaSe 2 is a much shallower donor than Ga In , suggesting that only Ga In can act as a detrimental recombination center in wide‐gap absorbers . In fact, the presence of intrinsic Ga Cu donor defect was experimentally confirmed in CuGaSe 2 by low‐temperature photoluminescence studies . On the other hand, Hanna et al found that the density of a deep acceptor in the absorber bulk is the lowest for samples with GGI ≈ 0.26, which also exhibit the lowest V OC losses, while its density increases monotonously for higher GGI values, resulting in V OC saturation .…”
Section: Introductionmentioning
confidence: 99%
“…12 In fact, the presence of intrinsic Ga Cu donor defect was experimentally confirmed in CuGaSe 2 by low-temperature photoluminescence studies. 13,14 On the other hand, Hanna et al found that the density of a deep acceptor in the absorber bulk is the lowest for samples with GGI ≈ 0.26, which also exhibit the lowest V OC losses, while its density increases monotonously for higher GGI values, resulting in V OC saturation. 15,16 An alternative explanation for the observed V OC vs E g trend is an increased grain boundary recombination due to Cu-enrichment in grain boundaries (ie, no hole repulsion) for Ga-rich compositions.…”
mentioning
confidence: 99%
“…Several approaches have been developed to combine Cu-rich absorbers with a Cu-poor surface by implementing different surface treatments [11,16,[19][20][21] that were reported to increase the V OC of Cu-rich cells through the reduction of interface recombination. Recently, it was found that the V OC gap between Cu-rich and Cu-poor cells is related to the bulk recombination and not only to the interface: the quasi-Fermi-level splitting (qFLs), that represents the highest V OC an absorber can achieve, is lower for Cu-rich Cu(In, Ga)Se 2 than for Cu-poor Cu(In, Ga)Se 2 , even before the interface with the buffer is formed [22,23]. The same study demonstrated a considerably larger difference between qFLs and V OC in Cu-rich solar cells, indicating that interface recombination poses an additional loss mechanism in Cu-rich Cu(In, Ga)Se 2 .…”
Section: Introductionmentioning
confidence: 99%